Forest condition monitoring in Finland : national report 2002-2005 - Merilä, Päivi, 1964-; Kilponen, Tuire; Derome, John, 1947- (Helsinki : Finnish Forest Research Institute, 2007)
Yhteenveto.
XLUETTELOITU
Keywords: ympäristön tila; metsävauriot; metsätuhot; metsät; metsämaa; laskeumat; kunto; ilman epäpuhtaudet; harsuuntuminen